Epic road trips of the Americas : explore Americas' most thrilling driving adventures - Balfour, Amy C. (Lonely Planet guidebooks., 2022)
Showcasing 50 of the Americas' greatest road trips across North and South America as well as the Caribbean, you'll discover classic drives including the Pacific Coast Highway, Gaspesie Loop in Canada and the Hana Highway in Hawaii, plus lesser-known routes. We cover a huge variety of themes and experiences across drives that range from a few hours to a week or more.